Islam dan Pancasila: Dialektika Hukum Tata Negara dalam Pemikiran Ali Hasjmy - Amiruddin Ahmad, Mukhtar; Hafniati, Hafniati; Abdurrahman Usman, Zulkifli (Tasyri' : Journal of Islamic Law, 2025)
This study examines Islam and Pancasila: The Dialectic of Constitutional Law in the Thought of A. Hasjmy. The purpose of this research is to reveal A. Hasjmy's thoughts related to Pancasila as the basis of the state and its relationship with Islam. This research method is qualitative by using descriptive analysis of A. Hasjmy's thoughts related to Islam, the state, and Pancasila. The analysis of A. Hasjmy's thought is analyzed using the heurmenetic method of trying to reveal the symbols of the text narrative expressed by A. Hasjmy. The data collection method of this study includes library research. Based on  the library research method, the  primary data in this study is a book by A. Hasjmy entitled Where is the Islamic State Located. This study shows that A. Hasjmy's thinking is modernist and adaptive. Modernist, A. Hasjmy's thinking is open and rational. Adaptive, A. Hasjmy is socially mature in understanding state culture. Pancasila, according to A. Hasjmy, is conceived with Islam; both divine teachings and social teachings. The precepts contained in Pancasila accommodate Islamic values. Indonesia, according to A. Hasjmy, has adhered to the principle of an Islamic state in the context of value substance based on Pancasila.